A Meta-Analysis of Audit Fees Determinants: Evidence from an Emerging Market - Ali Daemigah (Iranian Journal of Accounting, Auditing & Finance)
Using meta-analysis, we investigate the combined effect of the most extended independent variables in this literature line. The meta-analysis obtained results in a deeper understanding of the anomalies, mixed results, and gaps in audit fees research.To achieve the desired objective, meta-analysis is used. The study's statistical population reviewed the most relevant studies on this subject published in Iranian and international journals for the 2000-2016 period. The effect of independent variables on audit fees is studied. A total of 162 studies, 146 published in international journals, and 16 in Iranian journals are considered the study sample.Our findings suggest that some independent variables have consistent results, several show no precise rhythm to the results, and some others only indicate significant results in specific periods or certain countries; variables of audit quality, accounting firm size, industry specialization of the firm, accounting firm tenure and client size are positively correlated with audit fees. However, we conclude that there is no significant relationship between the risk of client firm and audit fees.The current study is almost the first study conducted on the study's subject, and the results may help audit the profession.